The Significant Effect of Training Toward Loan Repayment Performance Among Borrowers - Ahmad, Othman; Abdul Rahim, Mohd Kamarul Irwan (2022)
Microfinance is the provision of microcredit, savings, and other financial services to the poor who cannot obtain credit from commercial banks due to a lack of collateral or other factors. The funds can be used to fund commercial activities like asset acquisition and business development. Borrowers who do not have access to traditional financial institutions can obtain a loan through microfinance. Loan defaults are caused by a variety of factors, including high interest rates, insufficient loan size, poor appraisal, a lack of monitoring, and incorrect client selection. This paper would like to confirm the importance of training in preventing repayment default. The study's primary goal was to see if education has a significant impact on borrowers' ability to repay their loans. As a strategy, a number of related articles are being sought on the website by using the term "training." According to the findings, proper training may aid in better repayment performance. As a result, we conclude that borrowers should be provided with training as a support tool to increase loan repayment. When disbursing funds, microfinance organisations should include training as one of the tasks for entrepreneurs to complete.